2013
DOI: 10.5433/1679-0359.2013v34n6supl1p3585
|View full text |Cite
|
Sign up to set email alerts
|

Selectivity of pesticides used in peach orchards on the larval stage of the predator Chrysoperla externa (Hagen)

Abstract: The selectivity of sixteen pesticides used in peach orchards in Brazil was evaluated on larvae of Chrysoperla externa (Hagen) (Neuroptera: Chrysopidae) in laboratory (25±1ºC, 70±10% RH and 14 hours photophase). The bioassays consisted on the exposure of larvae to fresh dry pesticide film applied on glass plates. Lenght of each development stage, the mortality, the fecundity and fertility of survival adults were evaluated. Pesticides were classified according to the total toxic effect in harmless (<30%), slight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
7
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
(14 reference statements)
4
7
0
Order By: Relevance
“…This lack of negative effects is attributed to higher adult emergence. Similar to the results of our study, Godoy et al (2004) and Castilhos et al (2013) obtained mortalities of 100% and 94.6%, respectively, for exposure of 1st-instar C. externa larvae to deltamethrin.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This lack of negative effects is attributed to higher adult emergence. Similar to the results of our study, Godoy et al (2004) and Castilhos et al (2013) obtained mortalities of 100% and 94.6%, respectively, for exposure of 1st-instar C. externa larvae to deltamethrin.…”
Section: Discussionsupporting
confidence: 92%
“…Nasreen et al (2005a) and Toda and Kashio (1997) also found that fungicides had no toxic effects on larvae of C. carnea at any stage. A similar result was also obtained by Castilhos et al (2013).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Theoretically, few studies have been addressed that all developmental stages (eggs, larva, pupa, and adult) of green lacewing are susceptible to insecticides, the exposure may lead to lethal and sub-lethal effects [7,12]. Most of the studies highlighted lethal and sub-lethal effects of selective insecticides on larvae and adult lacewing [13][14][15], and some have focused on eggs and pupae that can be considered more tolerant to insecticides [6,16,17].…”
Section: Introductionmentioning
confidence: 99%